Strong Enhancement of PbS Quantum Dot NIR Emission Using Plasmonic Semiconductor Nanocrystals in Nanoporous Silicate Matrix. Issue 6 (26th January 2018) - Litvin, Aleksandr P.; Babaev, Anton A.; Dubavik, Aliaksei; Cherevkov, Sergei A.; Parfenov, Peter S.; Ushakova, Elena V.; Baranov, Mikhail A.; Andreeva, Olga V.; Purcell‐Milton, Finn; Gun'ko, Yurii; Fedorov, Anatoly V.; Baranov, Alexander V.
Abstract: Strong enhancement of near‐infrared (NIR) emission of lead sulfide quantum dots (QDs) induced by Cu2− x Se semiconductor plasmonic nanocrystals (PNCs), both embedded into nanoporous silicate matrix is reported. The emission enhancement comes from resonant interaction of QD optical transition dipole with the near field of plasmons of semiconductor PNCs. Possible mechanisms of QD photoluminescence broadening and shift, including Rabi splitting and trap‐state‐related photoluminescence enhancement, are considered. As a result, a novel optical luminescent material, which can be used as an efficient source of NIR emission is demonstrated. Abstract : PbS quantum dots and semiconductor plasmonic nanocrystals are both embedded into nanoporous silicate matrix. Resonant interaction of PbS quantum dots and semiconductor plasmonic nanocrystals induces strong enhancement of the near‐infrared emission of quantum dots. The enhancement factor reaches 20.0 for the resonant excitation at 1064 nm.